(untitled) (The International Research Journal of Management Science, 2022)
This paper provides the importance of the critical thinking among the student, which starts from the classroom. It also provides an overview of teachers’ perceptions and practices of it while teaching. Further, it also brings to the fore the necessity of integrating it in the classroom by the teachers. This qualitative study was conducted under Habermas’s interests’ approach with purposeful sampling technique as a methodology. Data was collected through in-depth interviews with teachers who have more than five years of experience in the academic field. The findings of the research provided insight that education though has gone through paradigm shift, from teacher centered to student centered, teachers still prefer practicing traditional teacher centered method depriving students of the critical thinking skills which they are in need of